Training needs of librarians in 100 state colleges and universities in the Philippines - Recalde, Hipolita Rea 1948-
This study determined the training needs of the librarians in the 100 colleges and universities in the Philippines. It used a structured questionnaire to gather data from the 193 respondents selected through stratified sampling. These respondents represented 70 of the 100 SUCs in the country.